2000
DOI: 10.1007/s005420050185
|View full text |Cite
|
Sign up to set email alerts
|

A micro cycloid-gear system fabricated by multi-exposure LIGA technique

Abstract: In this paper, a prototype of 2 mm-diameter micro-cycloid gear system fabricated by the multi-exposure LIGA technique is presented. The gear system is composed of a casing and three vertically stacked disks and gears. Each part consists of three different levels. The ®rst level, 40 lm high, was fabricated by UV-lithography, and the second as well as the third level, 195 lm and 250 lm high respectively, were processed by aligned deep X-ray lithography (DXL). The alignment error between two DXL-processed layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…High-aspect-ratio materials can be easily obtained on the microscale even if DXRL potential application can be extended to a submicrometer scale (Ehrfeld et al, 1999;Meyer et al, 2008). Another advantage of DXRL is that the lithography is not limited to two-dimensional structures, but complex three-dimensional shape materials (Katoh et al, 2001) such as optical components, micromechanical devices (Chung et al, 2000) and photonic crystals (Feiertag et al, 1997;Katsarakis et al, 2002) can also be fabricated. We have already demonstrated that the effect of hard X-rays on coating layers can be used to produce patterns in mesoporous (Falcaro et al, 2008(Falcaro et al, , 2009a, sol-gel (Falcaro et al, 2009b;, PE-CVD (Costacurta et al, 2010) and soft matter films (Innocenzi et al, 2010) and to generate in situ metallic nanoparticles in patterned structures.…”
Section: Introductionmentioning
confidence: 99%
“…High-aspect-ratio materials can be easily obtained on the microscale even if DXRL potential application can be extended to a submicrometer scale (Ehrfeld et al, 1999;Meyer et al, 2008). Another advantage of DXRL is that the lithography is not limited to two-dimensional structures, but complex three-dimensional shape materials (Katoh et al, 2001) such as optical components, micromechanical devices (Chung et al, 2000) and photonic crystals (Feiertag et al, 1997;Katsarakis et al, 2002) can also be fabricated. We have already demonstrated that the effect of hard X-rays on coating layers can be used to produce patterns in mesoporous (Falcaro et al, 2008(Falcaro et al, , 2009a, sol-gel (Falcaro et al, 2009b;, PE-CVD (Costacurta et al, 2010) and soft matter films (Innocenzi et al, 2010) and to generate in situ metallic nanoparticles in patterned structures.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters of reducer are as follow: motor power is 15kw, motor rotate speed is 1000r/min, transmitting ratio is 34, and transmitting efficiency is 94%. [5,6] Dynamic Meshing Strength Analysis.…”
Section: Transmission Error Analysismentioning
confidence: 99%
“…High aspect ratio materials can be easily obtained in the microscale but the potentiality of application of the technique extends to the nanoscale 7. Another advantage of DXRL is that the lithography is not limited to 2D structures, in fact, complex 3D shape materials8 such as optical components, micromechanical devices9 and photonic crystals,10 can also be fabricated. Several applications in different fields have been demonstrated so far for DXRL and some products are presently on the market; specialized equipments are currently commercially available (see ref 11.…”
Section: Introductionmentioning
confidence: 99%